Vagal Flexibility during Exercise: Impact of Training, Stress, Anthropometric Measures, and Gender. (5th October 2020) - de Souza, Perciliany Martins; Rosário, Nacha Samadi Andrade; de Castro Pinto, Kelerson Mauro; Assunção, Poliana Elisa; de Oliveira, Fernando Luiz Pereira; Bearzoti, Eduardo; Souza, Gabriela Guerra Leal
Abstract : We evaluated the effect of physical training, stress, anthropometric measures, and gender upon the reactivity and recovery of the heart rate variability (HRV) during a cardiorespiratory test. Professors (N = 54 ) were evaluated using the following: physical training: time, frequency, and length of physical exercise; resting heart rate (HR); maximum HR; and recovery HR; stress: stress symptoms, work stress, vital events, and perceived stress; anthropometric measures: body mass index, waist circumference (WC), waist-hip ratio (WHR), and fat percentage (FP); and HRV before, during, and after the test. The HRV decreased during and increased after the test. Increased recovery HR was associated with the decreased vagal output during the test, and decreased recovery HR was associated with the increased posttest vagal input. The higher the work control and stress symptoms of men and the higher the perceived stress for both genders, the lower the vagal output during the test. The lower stress symptom and work control of men and the lower work demand of women were associated with the posttest vagal increase. The increased WC and decreased WHR of men were associated with the lower vagal output during the test and the lower posttest vagal increase. The lower FP also was associated with the greater recovery.